A bifunctional nanoplatform based on copper manganate nanoflakes for bacterial elimination via a catalytic and photothermal synergistic effect. (26th June 2020) - Guo, Zhirong; Liu, Yingnan; Zhang, Yalan; Sun, Xinyu; Li, Fan; Bu, Tong; Wang, Qinzhi; Wang, Li
Abstract : This work constructed a multifunctional nanoplatform based on positively charged copper manganate nanoflakes (CuMnO2 NFs) for combined catalysis and photothermal sterilization. Abstract : Bacterial infection has been recognized as one of the greatest threats to public health. In view of the continuous increase of bacterial resistance, constructing a collaborative bactericidal platform is a promising strategy to enhance the efficiency of antimicrobial agents. Herein, we report a facile, biocompatible and versatile nano-platform based on positively charged copper manganate nanoflakes (CuMnO2 NFs), which exhibits intrinsic peroxidase-like catalytic activity and excellent photothermal properties. The CuMnO2 NFs can bind with negatively charged bacteria via electrostatic interactions, and generate hydroxyl radicals (˙OH) through catalysis involving hydrogen peroxide (H2 O2 ) to make bacteria more susceptible to temperature. Introducing near-infrared light generates hyperthermia to fight against bacteria and enhances the peroxidase-like catalytic activity of the CuMnO2 NFs, thus producing more ˙OH to combat bacteria. The PTT-enhanced ˙OH synergistic antibacterial strategy exerts desirable antibacterial efficiencies of 98.78% and 99.92% against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) at a controlled low temperature (below 50 °C), without damage to healthy tissues. Animal experiments indicate that this synergistic treatment has a better therapeutic effect on S. aureus -infected wounds in mice, compared with either treatment by itself. Therefore, this work holds great promise for developing new synergistic antimicrobial strategies to treat bacterial infections.